Geoengineering at the "Edge of the World": Exploring perceptions of ocean fertilisation through the Haida Salmon Restoration Corporation. Issue 1 (15th May 2018) - Gannon, Kate Elizabeth; Hulme, Mike
Abstract : The Haida Salmon Restoration Corporation's (HSRC) 2012 ocean fertilisation experiment introduced a controversial geoengineering technology to the First Nations village of Old Massett on the islands of Haida Gwaii in British Columbia. Local debate centred on conflicting interpretations of the potential environmental impacts of the project and on the Corporation's attempts to align its public brand with the Haida name and proud identity of environmental stewardship. More broadly, the controversy illustrated long‐standing arguments about the desirability and feasibility of ocean fertilisation as a geoengineering response to the threat of anthropogenic climate change. Using the HSRC case, this paper reports a novel situated study of public perceptions of geoengineering that combines ethnographic engagement with Q‐methodology. Three distinct viewpoints on ocean fertilisation are revealed, shaped by the unique confluence of social, political, cultural and environmental circumstances of Haida Gwaii. These viewpoints on ocean fertilisation reflect different ideas held by local residents about planetary limits, about the way humans attain knowledge of natural systems and about the human values of, and responsibilities toward, nature. Although the revealed viewpoints are constructed through contextually specific local meanings, they engage with debates that emerge across a range of other geoengineering technologies and which reflect contested philosophical positions visible in wider environmental management and restoration discourses. The case of ocean fertilisation off the islands of Haida Gwaii may therefore provide a useful benchmark for reflexivity in geoengineering governance. Our case study shows that engaging with the situated beliefs and values that underpin human attitudes and responses towards novel geoengineering technologies is a sine qua non for good governance. Even so, our results suggest such technologies will likely always be contested given the diverse ways in which people understand human relations with the non‐human world. Abstract : The Haida Salmon Restoration Corporation's (HSRC) 2012 ocean fertilisation experiment introduced a controversial geoengineering technology to the First Nations village of Old Massett on the islands of Haida Gwaii. Local debate centred on conflicting interpretations of the potential environmental impacts of the project and on the Corporation's attempts to align its public brand with the Haida name and proud identity of environmental stewardship. Through analysis of this case study, locally specific meanings interact with familiar global discourses which situate ocean fertilisation within debates about other geoengineering technologies and connect "geoengineering" in Haida Gwaii with wider cultural meanings and literatures that consider the human relationship with nature. e00054